(untitled) (Comprehensive Journal of Science, 2025)
Pragmatic theory is concerned with the study of language within its social and communicative context, aiming to analyze speech and identify the function of utterances. Undoubtedly, the speech act constitutes an effective element in the pragmatic process, as every utterance operates within the system of illocutionary semantic phenomena in two directions: direct acts and indirect acts. Speech acts exert an influential force on sentence meanings and rely on spoken actions that seek to achieve illocutionary purposes, possessing perlocutionary goals through which the responses of the addressees can be identified. This study examines indirect illocutionary acts of the interrogative style, clarifying their value within pragmatic analysis. These acts fall under directive illocutionary acts in pragmatics, wherein the speaker aims to guide the addressee to perform a certain action and to exert influence upon them. The study focuses on Juz’ ‘Amma, which displays a clear multiplicity of interrogative forms and types, varying according to context and the diversity of addressees.